2015
DOI: 10.1007/s00066-015-0858-7
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin pathway involvement in ionizing radiation-induced invasion of U87 glioblastoma cells

Abstract: Our data demonstrate a pivotal role of the Wnt/β-catenin pathway in ionizing radiation-induced invasion of glioblastoma cells, and suggest that targeting β-catenin is a promising therapeutic approach to overcoming glioma radioresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…To test this hypothesis, the β-catenin protein expression was determined in the cytoplasm and nucleus of CNE-2 cells, and Western blotting analysis revealed an increase in the nuclear accumulation of β-catenin in the transfection and negative control groups. In a recent study, ionizing radiation was found to induce nuclear translocation and accumulation of β-catenin and enhance the TCF/LEF transcriptional activities in glioblastoma U87 cells, and degrading β-catenin significantly reduced cell invasion [59], which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…To test this hypothesis, the β-catenin protein expression was determined in the cytoplasm and nucleus of CNE-2 cells, and Western blotting analysis revealed an increase in the nuclear accumulation of β-catenin in the transfection and negative control groups. In a recent study, ionizing radiation was found to induce nuclear translocation and accumulation of β-catenin and enhance the TCF/LEF transcriptional activities in glioblastoma U87 cells, and degrading β-catenin significantly reduced cell invasion [59], which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…Fitting, in our experiment, radio-sensitive SW1463 cells responded with a significant downregulation of ALDH1A3 to radiation. Dong and colleagues demonstrated a role for Wnt/β-catenin signaling in radiation-induced invasion of glioblastoma cells (29). In their model, radiation mediated nuclear accumulation of β-catenin and an up-regulation of Wnt/β-catenin downstream genes.…”
Section: Discussionmentioning
confidence: 99%
“…In their model, radiation mediated nuclear accumulation of β-catenin and an up-regulation of Wnt/β-catenin downstream genes. Pathway inhibition abrogated the pro-invasion effects of radiotherapy (29). Similar to our approach, Ahn et al repeatedly irradiated lung cancer cells to obtain resistant cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear β‐catenin has been described as a key protein involved in radioadaptive response, including cell survival when exposed to ionizing radiation . Our immunofluorescence data indicated that β‐catenin redistribution from cell–cell contacts to the cytoplasm and β‐catenin concentration in the nucleus were elevated in cells exposed to RT, and that this nuclear accumulation of β‐catenin was attenuated when DHA was applied in combination with RT.…”
Section: Discussionmentioning
confidence: 58%